Terapi Kognitif Mampu Menurunkan Tingkat Ansietas Mahasiswa Tingkat III dalam Menghadapi Sidang Kti dan Uji Kompetensi - Sri Laela (Universitas Malahayati Lampung, 2023)
ABSTRACT Level III students of the Nursing Academy are at risk of experiencing anxiety, this is because at level three, they will face a Final Writing Test and a Nurse Competency Test, both of which must be passed in order to graduate as a professional nurse. They are worried that if they do not pass the KTI Session and the Competency Test, they will not be able to graduate. The purpose of this study was to determine the effectiveness of cognitive therapy on student anxiety in dealing with the KTI trial and the nurse competency test. The research method used is pre-post test design. The sample in this study were 83 level III students. The research was conducted from June to August 2022. Students' level of anxiety was measured using the Zung Self-rating Anxiety Scale (ZSAS) questionnaire. Characteristics of third-level students in facing the KTI Session and Competency Test experienced moderate anxiety. The results showed that there was a significant decrease in anxiety (p-value = 0.047) after receiving nursing care and cognitive therapy. Nursing interventions and cognitive therapy were able to reduce the anxiety of third-level students in facing the KTI Session and the Nurse Competency Test..Keywords: Anxiety, Cognitive Therapy, Competency Test ABSTRAK Mahasiswa tingkat III Akademi Keperawatan berisiko mengalami ansietas, hal ini dikarenakan saat tingkat tiga, mereka akan menghadapi Uji Sidang Karya Tulis Akhir dan Uji Kompetensi Perawat, yang keduanya wajib dilewati untuk dapat lulus menjadi seorang perawat yang professional. Mereka merasa khawatir jika tidak lulus Sidang KTI dan Uji kompetensi, maka mereka tidak dapat di wisuda. Tujuan penelitian ini untuk mengetahui efektifitas terapi kognitif terhadap ansietas mahasiswa dalam menghadapi sidang KTI dan uji kompetensi perawat. Metode penelitian yang digunakan pre – post test design. Sampel dalam penelitian ini adalah mahasiswa tingkat III sebanyak 83 orang. Penelitian dilakukan pada Juni – Agustus 2022. Mahasiswa di ukur tingkat ansietasnya dengan menggunakan kuesioner Zung Self - rating Anxiety Scale (ZSAS), Karasteristik mahasiswa tingkat III dalam menghadapi Sidang KTI dan Uji Kompetensi mengalami ansietas sedang. Hasil penelitian menunjukkan ada penurunan ansietas secara bermakna (p-value = 0,047) setelah mendapat tindakan keperawatan Ners dan terapi kognitif. Tindakan keperawatan Ners dan terapi kognitif mampu menurunkan ansietas mahasiswa tingkat III dalam menghadapi Sidang KTI dan Uji Kompetensi perawat. Kata Kunci: Ansietas, Terapi Kognitif, Uji Kompetensi